Corticosteroid Treatment Prevents Lipopolysaccharide-Induced Increase of ACE2 and Reduces Fibrin Degradation Products in Bronchoalveolar Lavage Fluid - Reindl-Schwaighofer, Roman; Eskandary, Farsad; Bartko, Johann; Heinzel, Andreas; Jilma, Bernd; Hecking, Manfred; Schoergenhofer, Christian (Frontiers in Medicine, 2022)
The assessment of systemic corticosteroid effects on intrapulmonary disease biomarkers is challenging. This retrospective evaluation of a human endotoxemia model quantified ACE2 and fibrin degradation product (FDP) concentrations in bronchoalveolar lavage fluid (BALF) samples from a randomized, double-blind, placebo-controlled study (NCT01714427). Twenty-four healthy volunteers received either 2x40mg intravenous dexamethasone or placebo. These doses were administered 12 hours apart prior to bronchoscopy-guided intrabronchial lipopolysaccharide (LPS) stimulation (control: saline into the contralateral lung segment). We quantified ACE2 concentration, the Angiotensin-II-to-Angiotensin-1-7 conversion rate as well as FDP in BALF six hours after LPS instillation. In placebo-treated subjects, LPS instillation increased ACE2 concentrations compared to unstimulated lung segments [1481 (IQR: 736-1965) vs. 546 (413-988) pg/mL; p=0.016]. Dexamethasone abolished the increase in ACE2 concentrations (p=0.13). Accordingly, LPS instillation increased the Angiotensin-II-to-Angiotensin-1-7 conversion capacity significantly in the placebo cohort, indicating increased enzymatic activity (p=0.012). FDP increased following LPS-instillation [8.9 (2.7-12.2) vs. 6.6 (0.9-9.6) ng/mL, p=0.025] in the placebo group, while dexamethasone caused a shut-down of fibrinolysis in both lung segments. LPS instillation increased ACE2 concentration, its enzymatic activity and FDP, which was mitigated by systemic dexamethasone treatment. Our results strengthen previously published findings regarding the efficiency of corticosteroids for the treatment of COVID-19-induced acute lung injury.